VO#029 Proposal for drainage box works rev.02 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmission of the proposal of cost amount against the execution and completion of drainage box works for BRACU new campus project.